An integrated assessment of water quality in a land reform settlement in northern Rio de Janeiro state, Brazil. Issue 3 (March 2019) - Portal, Thayana Paranhos; Pedlowski, Marcos Antonio; de Almeida, Cibele M.S.; Canela, Maria C.
Abstract: The Zumbi dos Palmares land reform settlement lacks modern facilities for water and sewage treatment. Local farmers often use shallow wells as alternative source of water supply, because the water table is reasonably high in the region. This work presents a multivariate analysis assessment of physicochemical and bacteriological parameters and pesticide residues in water samples collected from these shallow wells. The physicochemical parameters analyzed were: conductivity, pH, DOC (dissolved organic carbon), nitrate, turbidity, and bacteriological analysis measuring total and fecal coliforms. The results show non-compliance with Brazilian legal standards in most samples where low pH values were found, characterizing the presence of acidic waters. Another example of non-compliance is the presence of total and fecal coliforms in for drinking water in most of the samples and, in some cases, very high values (2, 400 CFU). Some wells showed high conductivity values, probably associated with a history of oceanic intrusion. Analyses determining the contamination by pesticides show the presence of ametrine, atrazine, methyl parathion, carbaryl and hexazinone. The concentration for these compounds ranged from 0.14 to 1.17 μg/L. Ordinance No 2914/2011 from the Brazilian Ministry of Health establishes the acceptable limits for atrazine and methyl parathion as 9 μg L −1 and 2 μg L −1 . None of these exceeded the allowable Brazilian and European limits. However, for the other two pesticides, the European Legislation (Council Directive) recommends the maximum allowable concentration of 0.1 μg L −1 and, 0.5 μg L −1 for total pesticides. Our samples that were above the quantifiable limit of 50 ng L −1, were also above the European limit values. Our results therefore suggest that water gathered from shallow wells at the Zumbi dos Palmares settlement is not proper for consumption without proper disinfection treatments.